THE ROLE OF HUMAN RESOURCES IN SCULPTING COMPETITIVE EDGE IN UNSTABLE VUCA ENVIRONMENTS - Thompson, Edward Julian; Marshall, Catherine Anne (International Research Journal of Arts and Communication, 2024)
This paper explores the strategic role of Human Resource Management (HRM) in creating a sustainable competitive advantage in the Volatility, Uncertainty, Complexity, and Ambiguity (VUCA) business environment. Through a literature review of articles found in various databases, the study found that HRM plays a crucial role in generating a sustainable competitive advantage in the VUCA environment. Effective selection, development, and support of a motivated workforce can significantly contribute to an organization’s performance and sustainability. Specific strategies for achieving a sustainable competitive advantage include promoting diversity, recruiting and selecting talents oriented toward innovation, performance management, and training and development. Successful businesses applying HRM strategies for achieving a sustainable competitive advantage include Amazon and Google. The paper identifies the challenging context of VUCA in which businesses operate and stresses the importance of making employees innovationoriented and flexible. The paper also presents the crucial role of HRM in generating opportunities for companies to develop their competitive advantage in the VUCA context through approaches like digitalization and talent acquisition.